Closure of patent foramen ovale for secondary prevention of cerebrovascular events - Wahl, Andreas; Meier, Bernhard (SA Heart Journal, 2017)
Stroke is the most debilitating cardiovascular event. It has a variety of causes that may be present simultaneously. In young or otherwise healthy people a patent foramen ovale (PFO) is increasingly searched for. In stroke of the elderly atherosclerosis and atrial fi brillation are in the foreground but the PFO should not be ignored. The risk of a PFO related stroke over time is controversial and so is its prevention by PFO closure. Percutaneous PFO closure is a minimally invasive procedure which can be performed with high success and low morbidity. We review the rationale for PFO closure for secondary prevention of embolic events.